Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Bangli - Aryanata, I Ketut Dimas; Andayani W, Rai Dwi (UNHI Press, 2025)
This study examines the role of the government in enhancing compliance with motor vehicle tax in Bangli Regency. Through a case study design, information was gathered by conducting comprehensive interviews with active taxpayers to explore their perceptions and experiences regarding government policies and programs. The findings indicate that government efforts, including mobile Samsat services, e-Samsat, and tax amnesty programs, have facilitated taxpayer compliance by providing accessible services and financial incentives. Continuous education through socialization, local media, and direct outreach further supports taxpayers’ understanding of the importance of timely tax payment. However, variations in taxpayer awareness, technical limitations in digital services, and socio-economic factors remain challenges that affect compliance. Overall, effective tax compliance requires a holistic strategy combining accessible services, ongoing education, persuasive approaches, and consistent supervision. These findings contribute to understanding the dynamics of taxpayer behavior and provide recommendations for improving government interventions to increase tax compliance.